A Study of Factors that Affect Learners’ English Writing Skill - Bestoon Saleh Ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Writing proficiency is a crucial part of language learning and plays a vital role in professional and educational settings. Writing tends to be viewed as , perhaps, the most difficult and demanding of the four skills, while listening, reading, and speaking are all significant skills. This is due to the fact that writing demands a high degree of proficiency in language, vocabulary, and grammar, as well as an ability to organize and communicate ideas clearly and cohesively. The present paper attempts to study the factors that positively affect learners ‘English writing skill in an academic context. It also aims to figure out the difficulties that students encounter in academic writing skill. This review study identifies a body of literature in terms of writing skill, writing problems, and writing-influencing factors. The review of the previous studies demonstrates that a few fundamental factors influence students’ skill to write professionally. Furthermore, there are a few noteworthy factors that hinder their academic writing skills. According to the literature review, the learners’ main goal is to boost their writing, and they require more time and attention. This study supports teachers as well as students in questioning the variables that strengthen writing skills.